A Suggested New Approach to the Measurement and Reporting of Gross Short- Term Borrowing Operations by Governments - Blommestein, Hans J.. (OECD Publishing, 2010)
As part of its Borrowing Outlook, the OECD estimates gross short- term government borrowing requirements. The article concludes that all methods for measuring short-term borrowing needs studied here - except one - provide either significantly underestimated or substantially overestimated measures. The article therefore suggests adopting the following measure: Gross Short-Term Marketable Borrowing Requirements is equal to Net Short-Term Borrowing Requirements plus the outstanding amount of the stock of short-term instruments. This new measure (referred to as Method 2 in the study) yields, in principle, meaningful estimates, comparable across different countries. JEL Classification: G15, G18, H63, H68. Keywords: measuring gross short-term borrowing requirements, debt
Keywords: Finance and Investment